Antidiabetic Activities of Broccoli Extracts (Brassica oleracea L.var italica) on Mice Induced Streptozotocin-Nicotinamide - Heni Lutfiyati; Fitriana Yuliastuti; Imron Wahyu Hidayat; Prasojo Pribadi; Sodiq Kamal (Journal of Tropical Pharmacy and Chemistry, 2018)
Several plant species have been used for the treatment of diabetes. Research on plants that can be used to treat diabetes such as Cinnamomum cassia and Cinnamomum zeylanicum, Piper sarmentosum Roxb, Nelumbo nucifera, Ceiba petandra Memecylon malabaricum. Broccoli (Brassica oleracea L var italics) is a flower of vegetables like cabbage plants. Broccoli juice is made capable of direct and indirect effects on the reduction of blood LDL; the indirect effect is by repairing pancreatic beta cells and increasing insulin sensitivity. The purpose of this study was to determine whether broccoli has activity as antidiabetic. The subjects consisted of 15 mice induced with nicotinamide 70 mg/kg BW and Stz 150 mg/kg BW. Diabetic mice were divided into the positive control group (glibenclamide), negative control group (CMC Na) and three treatment groups. The test material is broccoli extract dose 75 mg / kg BW, 150 mg /kg BW and 300 mg/kg BW given peroral for 14 days. Anova test results showed that there was a significant difference in the average percentage of decreased blood glucose levels in all treatments. The result of Post Hock Tukey HSD test with a 95% confidence level showed a significant difference in the negative control group compared with positive control group and extract 300mg / kg BW. This shows that positive control group and extracts 300mg / kg body weight have an activity to decrease blood glucose level.